Effects of the fungicides azoxystrobin, pyraclostrobin and boscalid on the physiology of Japanese cucumber - Amaro, Amanda Cristina Esteves [UNESP]; Ramos, Anamaria Ribeiro Pereira [UNESP]; Macedo, Ana Claudia [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Elsevier, 2018)
Strobilurins are fungicides with beneficial physiological effects on crop yield due to promotion of net carbon assimilation, nitrate reductase enzyme activity, stress tolerance and hormonal balance. The carboxamides complement the action of the strobilurins when applied alternately or together. This study aimed to evaluate the effect of application of pyraclostrobin, azoxystrobin and boscalid on grafted and ungrafted Japanese cucumber (Cucumis sativus L.) in order to analyze the effects of these fungicides on plant physiology and increased fruit production. The experimental design was completely randomized in a 2 × 5 factorial scheme, with grafted and ungrafted cucumber plants and 5 fungicide treatments: control; azoxystrobin 60 g a.i ha−1; boscalid 50 g a.i ha−1; pyraclostrobin 50 g a.i ha−1; and boscalid 100 g a.i ha−1 + pyraclostrobin 50 g a.i ha−1, applied 18 days after transplanting and then at intervals of seven days. The effect of the treatments was evaluated based on the average yield and fruit mass, in addition to observations of gas exchange, lipid peroxidation, and the activities of peroxidase, superoxide dismutase, catalase and nitrate reductase. Based on the results obtained, it was concluded that the fungicide treatments resulted in different responses between the grafted and ungrafted plants. The physiological benefits were more evident in the grafted plants treated with pyraclostrobin or boscalid alone, and these benefits manifested in terms of fruit production and increased the activity of the antioxidative system, thereby reducing stress. The higher productivity probably occurred due to the better physiological performance of these plants, mainly at the beginning of development, presenting greater activity of the enzyme nitrate reductase, in addition to the higher net CO2 assimilation and carboxylation efficiency.
Keywords: Carboxamides; Cucumis sativus L.; Physiological effects; Strobilurin